Analysis of the mechanism of skeletal muscle atrophy from the pathway of decreased protein synthesis - Chen, Peng; Jia, Fangfang; Wang, Meng; Yang, Shengbo (Frontiers in Physiology, 2025)
Skeletal muscle atrophy is associated with denervation, cancer, diabetes, aging, immobilization, and inflammation, which can significantly impair mobility. It is primarily attributable to increased protein catabolism alongside reduced protein synthesis, although the precise mechanisms underlying this process are not yet fully known. Unlike in the pathway driving increased catabolism, fewer studies have explored the mechanism underpinning muscle atrophy under reduced protein synthesis. Therefore, this study aimed to focus on summarizing relevant studies on the reduction of protein synthesis leading to skeletal muscle atrophy, as driven by alterations in pathways such as the insulin-like growth factor-1-phosphatidylinositol 3-kinase-protein kinase B-rapamycin signaling pathway, glycogen synthase kinase-3, glucocorticoids, 5′-adenosine monophosphate-activated protein kinase, branched-chain amino acid sensors, myostatin, long-term proinflammatory factors, oxidative stress and mitochondrial dysfunction, calciumion concentration, activating transcription factor 4, and glycyl-tRNA synthetase alterations. Consolidating these data will provide a foundation and theoretical basis for further investigation into the mechanisms of muscle atrophy from the perspective of reduced protein synthesis pathways.